PENGEMBANGAN BAHAN AJAR ELEKTRONIK MENGGUNAKAN APLIKASI FLIP PDF CORPORATE EDITION PADA PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Rico Aulia Rahman; Mai Sri Lena (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
The research objective is to develop and produce electronic teaching material products using applications Flip PDF Corporate Edition in learning Theme 6(Heat and Its Transfer) Sub-theme 1(Temperature and Heat) in learning 3 class V (Five) SDN 12 Kampung Durian, Padang City. Research development also aims to see the validity and feasibility of the electronic teaching materials that have been developed. Development of electronic teaching materials using applications Flip PDF Corporate Editions tudied using the ADDIE model which consists of five stages namely Analysis, Design, Development, Implementation, Evaluation. Research on the development of electronic teaching materials begins with analyzing class needs, designing or designing electronic teaching materials, then carrying out the development of electronic teaching materials, then conducting validation by experts, revising electronic teaching materials. After carrying out revisions from experts, implementation of electronic teaching materials with predetermined subjects was carried out. The average of the validation values by the material, language, and teaching material validators shows that electronic teaching materials can be used in the learning process with an overall score of 94.17% validation percentage with 95% material validation results, 90% language validation results and material validation results teaching 97.5%. In the implementation and practicality stages, the response from the teacher and students was very good for the electronic teaching materials that had been used. The result of the teacher's response is 97.14%. And students 96.4%. From the research results it can be concluded that electronic teaching materials use applications Flip PDF Corporate Edition has been valid, very interesting, and appropriate for students to use in the learning process